Distribution Characteristics and Environmental Responses of Benthic Diatoms in Reservoirs in Headstream Area of Le'an River - JIN Yi; WANG Hao; YAN Ruyu; JI Yong; HU Qiannan; BAI Dongchen (Renmin Zhujiang)
This study aims to investigate the community distribution characteristics of the benthic diatom species in the reservoirs in the headstream area of the Le'an River and the response relationships of those species with environmental factors.For this purpose,the composition and water physicochemical parameters of benthic diatom communities in Datangwu reservoir,Qinghua reservoir,and Shijing reservoir in Wuyuan County were measured in the winter of 2020.Pearson correlation analysis and redundancy analysis were performed to explore the spatial distribution characteristics of benthic diatoms and the abovementioned response relationships.The results show that a total of 73 species,belonging to 24 genera,of diatoms are detected from 11 sampling sites.Specifically,the abundance of the dominant species Cyclotella stelligera is 21.91%,and the Melosira,Cocconeis,and Achnanthes genera are widely distributed.The following observations can be made from the analysis of the distribution characteristics and environmental responses of the diatoms:The relationship between Melosira varians and water eutrophication level is significant;a marked positive correlation is observed between Cyclotella stelligera and CODMn;Cymbella perpusilla and total phosphorus (TP) are negatively correlated.NH+4-N and NO-3-N are significant factors affecting the differences among diatom genera and species,altogether explaining 43.1% of the diatom information.A preliminary determination is made that the structure of the benthic diatom communities in the reservoirs in the headstream area of the Le'an River responds simultaneously to NH+4-N,NO-3-N,CODMn,TP,and other parameters.